2018
DOI: 10.1186/s12943-018-0890-1
|View full text |Cite|
|
Sign up to set email alerts
|

Proteogenomic characterization and comprehensive integrative genomic analysis of human colorectal cancer liver metastasis

Abstract: BackgroundProteogenomic characterization and integrative and comparative genomic analysis provide a functional context to annotate genomic abnormalities with prognostic value.MethodsHere, we analyzed the proteomes and performed whole exome and transcriptome sequencing and single nucleotide polymorphism array profiling for 2 sets of triplet samples comprised of normal colorectal tissue, primary CRC tissue, and synchronous matched liver metastatic tissue.ResultsWe identified 112 CNV-mRNA-protein correlated molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 26 publications
3
49
0
1
Order By: Relevance
“…Sequences of PCR primers are shown in the Additional file 1 : Table S1. U6 and GAPDH were used as the endogenous controls, and the 2 -ΔΔCT method was used to analyze expression levels [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sequences of PCR primers are shown in the Additional file 1 : Table S1. U6 and GAPDH were used as the endogenous controls, and the 2 -ΔΔCT method was used to analyze expression levels [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, NEUROD1/2 functions as growth-promoting gene in HPNE cells, but as suppressor of proliferation in HMEC cells (Sack et al, 2018). DMRT like family B with proline rich C-terminal 1 (DMRTB1) mutation might relate to human colorectal cancer liver metastasis (Ma et al, 2018). Ahmadreza Niavarani et al found that strong expression of apolipoprotein B mRNA editing enzyme catalytic subunit 1 (APOBEC1) was associated with short survival time in pan-cancer, which was in line with our result (Niavarani et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CCT6A protein expression levels are elevated in tumor tissues of patients with hepatocellular carcinoma and that the overall survival of these patients is relatively shorter [5] . Previous studies have also con rmed that the number of mutant peptides has potential prognostic value, with somatic variants showing increased expression of CCT6A, which has clinical signi cance [6] . CCT6A is expression-inducible and ampli cation-inducible in glioblastoma, and shows a signi cant negative correlation with survival [7] .…”
Section: Introductionmentioning
confidence: 92%